(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The front desk employees are responsible for a vital function in the hotel. The workforceconsists of a front desk clerk, a cashier, a reservations clerk, a manager, a concierge, a night auditor, atelephone operator, bell crew, and elevator operation. According to meeting and greeting guests,providing information during their stay, and processing their departure, including payment, are theprimary focuses of front office, which is taken to include those areas of activity that centre on thereception desk and its allied areas. The Internet, the Business Centre and Conference Room Facilities,Prompt Round-the-Clock Room Service with a Variety of Items on the Menu, and the Ambience and MenuVariety in the Restaurants are some of the highlights of this hotel. According to the findings of the study,there is a disparity between the expectations (importance) of guests and the satisfaction (performance)of guests regarding the Reception and Room facilities, Room Service, and Food and Beverage Outlets.This indicates that guests were not as satisfied as they had anticipated being with the hotels.